Factors Affecting the Referral Time to Nephrologists in Patients With Chronic Kidney Disease: A Prospective Cohort Study in Korea - Lee, Jeonghwan (Medicine (Baltimore), 2016)
Timely referral to nephrologists is important for improving clinical outcomes and reducing costs during transition periods. We evaluated the impact of patients’ demographic, clinical, and social health characteristics on referral time. A total of 1744 CKD patients who started maintaining dialysis were enrolled in a Korean prospective cohort. The early referral (ER) and late referral group (LR) were defined as patients who were referred to a nephrologist more than or less than 1 year prior to dialysis initiation, respectively. A total of 1088 patients (62.3%) were in the ER, and 656 patients (37.6%) were in the LR. Among the patients in the LR, 398 patients (60.7%) were referred within the 3 months prior to the start of dialysis (ultralate referral group [ULR]). The ER was younger at the time of referral than the LR; however, the ER was older at the start of dialysis. Patients with diabetes or hypertension as the cause of kidney disease were more common in the LR, whereas patients with glomerulonephritis, females, and nonsmokers were more common in the ER. The ER had more well-controlled blood pressure, lower phosphorus levels, and higher hemoglobin levels at the start of dialysis. Congestive heart failure (CHF) was more common in the LR. In the multivariate analysis, male sex (odds ratio [OR] 1.465, 95% confidence interval [CI] 1.034–2.076), underlying kidney disease (diabetes mellitus [OR 1.507, 95% CI 1.057–2.148] and hypertension [OR 1.995, 95% CI 1.305–3.051]), occupation (mechanician [OR 2.975, 95% CI 1.445–6.125], laborer [OR 3.209, 95% CI 1.405–7.327], and farmer [OR 5.147, 95% CI 2.217–11.953]), CHF (OR 2.152, 95% CI 1.543–3.000), and ambulatory status (assisted-walks, OR 2.072, 95% CI 1.381–3.111) were proved as the independent risk factor for late referral. Patients with hypertensive or diabetic kidney disease are referred later than those with glomerulonephritis. Male patients with physically active occupations exhibiting CHF and restricted ambulation were associated with a late referral. Considering the various factors associated with late referral, efforts to increase early referrals should be emphasized, particularly in patients with hypertension, diabetes, or congestive heart failure.